Estudo sobre o transporte de cobre em solo arenoso laterítico estabilizado com fosfogesso e bentonita - Ferreira, Eduardo Silva (2020)
The compacted soil barriers are currently one of the most used processes for building liners in landfills. Dimensioning these containment structures requires the knowledge of contaminant transport parameters in porous media, such as adsorption, which acts to delay the movement of the contaminant, and diffusion, a mechanism that dominates the contaminant transport process when one works with low permeability. Thus, the objective of this work was to experimentally obtain the Cu2+ retention capacity in a lateritic sandy soil stabilized with phosphogypsum and bentonite. For this, tests were performed on Soil (S) and lateritic sandy soil with 10% phosphogypsum (SF), lateritic sandy soil with 6% bentonite (SB6) and lateritic sandy soil with 10% phosphogypsum and 6% bentonite (SFB6), with Cu2+ concentrations varying between 0 and 800 mg/L. Chemical, physical and mineralogical characterization tests were performed for soil, SF, SB6 and SFB6 tests, indirect compatibility tests to evaluate the interaction between Cu2+ and the materials and batch test to obtain the adsorption capacity. The diffusion tests were carried out with the soil, SB6 and SFB6 compacted in the water ratio and maximum specific weight in the normal Proctor energy. The chemical, physical and mineralogical characterization tests demonstrated that the stabilization of the soil with bentonite reduced the pores of the macrostructure, but kept the characteristics of the soil intact. The phosphogypsum increased the availability of Ca2+ by raising the CTC of the materials up to 8.36 times in relation to the soil, however the Ca2+ made available was not available for ion exchange, in addition, the phosphogypsum acted in a way against the bentonite, increasing the diameters pores in certain PSD strips. The indirect compatibility analyzes show that Cu2+ acted in order to aggregate the particles of the soil and of the SB6 mixture, but showing itself compatible with the materials used. The results of batch tests showed that the stabilization causes an increase in the retention capacity by the materials, with the following removal order SB6> SFB6> SF> S, with stabilization with bentonite being more efficient than phosphogypsum. The diffusion cells constructed were efficient for carrying out tests with compacted soil. The use of stabilizers improved the ability to attenuate the diffusive transport of Cu2+, where the soil allowed a greater advance of Cu2+ with a lower reduction in concentration in the reservoir, SFB6 showed a reduction in the concentration of the reservoir close to the soil, however with less advances of concentrations in the liner and finally the SB6 showed a greater reduction in concentration in the reservoir and greater immobilization of the contaminant in the first layer compared to other materials. In this way, the adsorption and diffusion tests demonstrate that the use of stabilizers improved the ability to attenuate the transport of Cu2+, and it is recommended to use them in geoenvironmental works designed to retain Cu2+ ions.